2011
DOI: 10.1093/ndt/gfr629
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric dimethylarginine may mediate increased heat pain threshold in experimental chronic kidney disease

Abstract: Induction of progressive renal failure in rats by 5/6 nephrectomy, which is accompanied by a marked increase of the serum levels of the endogenous NOS inhibitor ADMA, leads to a significantly increased heat pain threshold at 28 days. The sole infusion of ADMA into healthy rats leads to the same increase in heat pain threshold.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…A recent study reported that ADMA might affect nociception in CKD [29]. As mentioned above, our results show that serum ADMA levels increased in FD.…”
Section: Discussionsupporting
confidence: 84%
“…A recent study reported that ADMA might affect nociception in CKD [29]. As mentioned above, our results show that serum ADMA levels increased in FD.…”
Section: Discussionsupporting
confidence: 84%
“…69 In clinical studies, ADMA levels are increased in diabetic polyneuropathy. 70 High ADMA levels in CKD patients also are related to high-frequency hearing loss.…”
Section: Experimental and Clinical Data On Admamentioning
confidence: 99%
“… 86 Interestingly, in an animal model of renal failure, infusion of ADMA in healthy rats or in those with nephrectomy (inducing renal failure) resulted in increase of thermal pain threshold. 87 ADMA levels are also increased in SCD 49 and will impact arginine bioavailability. It is unknown what role, if any, ADMA has on pain in SCD, but it will be evaluated in future studies.…”
Section: Arginine In Painmentioning
confidence: 99%